Comparative Skeletal Anatomy A Photographic Atlas for Medical Examiners, Coroners, Forensic Anthropologists, and Archaeologists - Adams, Bradley J.; Crabtree, Pamela J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Forensic scientists working with human skeletal remains must be able to differentiate between human and non-human bones. Comparative Skeletal Anatomy: A Photographic Atlas for Medical Examiners, Coroners, Forensic Anthropologists, and Archaeologists fills a void in the literature by providing a comprehensive photographic guide of both human and non-human bones that is useful to those working in the fields of archaeology or the forensic sciences. This volume is a photographic atlas of common animal bones and is the first to focus comparatively on both human and animal osteology. Throughout this groundbreaking text, animal bones are photographed alongside the corresponding human bone, allowing the reader to observe size and shape variations. The goal of this guide is to help experienced archaeologists and forensic scientists distinguish human remains from common animal species, including horses, cows, goats, rabbits, chickens, ducks, sheep, and pigs, among others. Comprehensive and timely, Comparative Skeletal Anatomy: A Photographic Atlas for Medical Examiners, Coroners, Forensic Anthropologists, and Archaeologists is sure to become an essential reference for all forensic scientists and archeologists working with human skeletal remains.
Human vs Horse -- Human vs Cow -- Human vs Bear -- Human vs Deer -- Human vs Pig -- Human vs Goat -- Human vs Sheep -- Human vs Dog -- Human vs Raccoon -- Human vs Opossum -- Human vs Cat -- Human vs Rabbit -- Human vs Turkey -- Human vs Duck -- Human vs Chicken -- Miscellaneous -- Traces of Butchery and Bone Working.
Keywords: Forensic medicine; Human anatomy; Human physiology; Animal physiology; Forensic Medicine; Anatomy; Human Physiology; Animal Physiology